A General Overview of Mesenchymal Stem Cell Therapies in Drug- and Chemical-Induced Liver Injury Models - Müşerref Şeyma Ceyhan; Suna Ömeroğlu; Zeynep Yığman (Gazi Medical Journal)
Liver injury is commonly seen in the population depending on the drug and chemical usage. Different groups of drugs and chemicals lead to different pathogeneses in the liver, such as necrosis, fibrosis, or inflammation. Although the liver has a high regenerative capability, drug- and chemical-induced liver injury may result in organ failure. Because of the limitations of liver transplantation, therapy methods alternative to organ transplantation still need to be studied. Owing to their differentiation and regeneration abilities, mesenchymal stem cells (MSCs) have recently drawn attention as potential therapeutic agents. In this review, we focused on the effects of human MSCs derived from adipose tissue, bone marrow, umbilical cord, placenta, and amniotic membrane on drug- and chemical-induced liver injury models. Recent studies have reported recovery by the application of human MSCs from different sources. Although MSC therapy leads to amelioration in liver function, researchers still try to improve therapeutic efficacy. To this end, different modifications and application modalities of MSCs were investigated in drug-induced liver injury models. To understand the molecular mechanisms of MSCs’ effects on liver injury, animal studies are required to drive research perspectives for future progress.